The internet of things communication protocol for devices with low memory footprint. (2017) - VinkoviÄ, SaÅ¡o; OjsterÅ¡ek, Milan
This paper describes a new communication protocol named extensible markup connectivity (XMC) which is designed for the transmission of messages between an embedded device and a remote system. A new language called extensible markup device descriptor (XMDD) has also been developed and is used to describe the functional profile of the embedded device. The main advantage of the XMC protocol is its flexibility and independence from the device type. It is suitable for communication with devices that have a curtailed amount of working memory (a few kB) and limited computing power, i.e., 8-bit or 16-bit microcontrollers. The interference with the basic source code of the embedded device is not needed and the access to all exposed functionalities of device is enabled. The protocol also maintains a low production price for the connected embedded device and provides a flexible upgrade of software without any redundancy input.